(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
This study was conducted on cattle milk production characteristics among agro-pastoralists in North West Nigeria. The study described the socio-economic distribution of cattle milk producers and evaluated the cattle milk production techniques in the study area. A three stage (multi-stage) sampling technique involving a combination of purposeful, random and snow ball sampling were used to select 157 respondents. Data were collected from sampled population using structured questionnaire. The data obtained were analysed using descriptive statistics which include frequency counts and percentages. The study showed that most of the respondents (81.3%) were involved in rearing of cattle used for milk production as agro-pastoralists. The overall average number of cattle per herd in the study area was 17 heads of cattle. Labour for extraction of milk was majorly provided by men (80.6%) based on the overall analysis of the four States considered. Average milk per herd per day is 9 litres. About 24% of the respondents however obtained more than 15.5 litres of milk per herd per day. The milk production among agro-pastoralists in this study is characterized with low output of 9 litres per day. However, the agropastoralists in North West Nigeria have great potentials of youthful age of milk producers (average of 36 years) and long years of experience in milk production. Technologies for increased milk productivity like feeding balanced ration, breeding and selection of improved stocks, adequate health care and disease control need to be packaged and promoted among agro-pastoralists in North West Nigeria.